2016
DOI: 10.1073/pnas.1616206113
|View full text |Cite
|
Sign up to set email alerts
|

Calcium sensor regulation of the Ca V 2.1 Ca 2+ channel contributes to long-term potentiation and spatial learning

Abstract: Many forms of short-term synaptic plasticity rely on regulation of presynaptic voltage-gated Ca 2+ type 2.1 (Ca V 2.1) channels. However, the contribution of regulation of Ca V 2.1 channels to other forms of neuroplasticity and to learning and memory are not known. Here we have studied mice with a mutation (IM-AA) that disrupts regulation of Ca V 2.1 channels by calmodulin and related calcium sensor proteins. Surprisingly, we find that long-term potentiation (LTP) of synaptic transmission at the Schaffer colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Furthermore, the impairments in short-term and long-term plasticity due to Ca V 2.1 channel mutation at the IQ-like motif are associated with pronounced deficits in spatial learning and memory in context-dependent fear conditioning and in the Barnes circular maze. Thus, regulation of Ca V 2.1 channels by CaM and nCaS is required for not only presynaptic facilitation but also induction of postsynaptic long-term potentiation, and spatial learning and memory [136].…”
Section: Neuronal Firing and Presynaptic Short-term Plasticitymentioning
confidence: 99%
“…Furthermore, the impairments in short-term and long-term plasticity due to Ca V 2.1 channel mutation at the IQ-like motif are associated with pronounced deficits in spatial learning and memory in context-dependent fear conditioning and in the Barnes circular maze. Thus, regulation of Ca V 2.1 channels by CaM and nCaS is required for not only presynaptic facilitation but also induction of postsynaptic long-term potentiation, and spatial learning and memory [136].…”
Section: Neuronal Firing and Presynaptic Short-term Plasticitymentioning
confidence: 99%
“…Although the reason for the reduced Ca V 2.1 channel density in some cell types in Ca IM-AA mice is not known, even a small decrement in calcium channel density can strongly reduce the initial synaptic strength, which in turn increases synaptic facilitation. These results raise the possibility that changes in Ca V 2.1 channel density in some types of neurons could contribute to behavioral phenotypes that have been observed in Ca IM-AA mice (Nanou et al, 2016b, 2016c). We note however that a reduction in Ca V 2.1 current density is only one factor that may influence the balance of synaptic depression and facilitation in Ca IM-AA animals.…”
Section: Discussionmentioning
confidence: 73%
“…Our electrophysiological study, following changes in EPSP after an AP, showed that release-ready SVs are controlled by the millisecond Ca 2+ dynamics [ 86 ] that activate multiple protein cascades via Ca 2+ -sensor molecules, including AZ proteins complex, motor proteins, and endocytic proteins [ 56 , 64 , 85 ] ( Figure 7 ). Furthermore, the millisecond Ca 2+ dynamics also control presynaptic Ca 2+ channels activity, by Ca 2+ bound CaM and neuron-specific Ca 2+ -binding proteins [ 121 , 141 , 148 , 151 ], to modulate Ca 2+ elevation with incoming APs. These multiple protein cascades activated by a single AP should be activated during and after bursts of APs, resulting in presynaptic short-term plasticity.…”
Section: Resultsmentioning
confidence: 99%